Phytoremediation potential of the naturally occurring wetland species in protected Long Beach in Ulcinj, Montenegro - Milić, Dubravka; Bubanja, Nada; Ninkov, Jordana; Milić, Stanko; Vasin, Jovica; Luković, Jadranka (The Science of the total environment, 2021)
Long Beach, situated in southern Montenegro, is subject to considerable biogenic and abiogenic influences. Thus, analyzing total heavy metal content in soil and plants in this region is, while challenging, highly important in order to assess the level for determining the soil degradation level and the phytoremediation potential of naturally growing salt marsh species. This area together with a Bojana river and backshore forms a real vegetation mosaic where habitats of various types coexist. Therefore, it represents good model system. In the present study, the levels of As, Al, B, Cd, Co, Cr, Cu, Hg, Fe, Mn, Mo, Ni, Pb and Zn in coastal soils as well as in eight salt marsh plants: Bolboschoenus maritimus, Juncus acutus, Juncus anceps, Juncus articulatus, Juncus gerardii, Juncus maritimus, Scirpus holoschoenus and Schoenus nigricans, were investigated in order to identify the plant species that can be used for the remediation of polluted sites, especially those located along the coastline. The obtained results show that species J. gerardii, J. articulatus and B. maritimus can be clearly separated from J. acutus, J. anceps, J. maritimus, S. holoschoenus and Sh. nigricans based on the degree of heavy metal accumulation in various organs. Moreover, analyses revealed that the bioaccumulation factor of underground organs is significantly higher relative to that of the aboveground parts for almost all investigated metals and species. The bioaccumulation factor had the highest value in the underground organs of J. gerardii and B. maritimus, where a value of 3.37 was measured for B and 2.54 for Hg, respectively. Hence, as all investigated species are “underground accumulators” for most of the analyzed metals, they could be useful for phytostabilization and phytoremediation of B and Hg in particular. Moreover, each plant species can be used in the phytoremediation process targeting specific heavy metals. [Display omitted] •Pollution of heavy metals was examined in eight wetland species and costal soil.•Bioaccumulation and translocation of heavy metals are species specific.•Underground organs have the higher bioaccumulation potential.•Phytoremediation potential is given for each plant species.